Evaluation of Some Serum Antioxidants in Mandibular Bone Defect Healing in Rabbits Orally Supplemented with Pomegranate Peel Extract - Sarchil Ezadeen Mohyadeen; Rezan Majeed Omer; Bakhtiar Muhialdin Ahmed (Diyala Journal of Medicine, 2021)
Background: Pomegranate (PG) fruit (punicagranatum L, Punicaceae contains many bioactive substances that play important role in the treatment of a variety of medical problems. Among PG parts, it was observed that the peel had the most potent antioxidant activity.